(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2022)
This study aims to study the comparative results of the application of the classical academic and modern dynamic types of studying Chinese writing in its pragmatic aspect. Chinese language and writing are among the most difficult to learn as a second language, requiring advanced teaching methods with wider use of elements of the digital environment and the student’s independent active use of web services for active language learning. This aspect is also important when using more and more mass distance learning. The study involved 90 students aged 23 years old to 35 years old, who were equally divided into experimental and control groups. The experimental group used active learning methods and the control group used the usual academic methods of teaching Chinese writing, in accordance with the university course. The training was allocated four hours per week for remote training (using the Google Meet platform). The results demonstrated that the dynamic approach is effective in teaching hieroglyphics and pragmatic aspects of the language (reading, typing on a computer, listening comprehension, recognising words and written hieroglyphs). The academic classroom method is more suitable for the formation of correct pronunciation, taking into account the tonal type of Chinese phonetics.